Fluid Therapy During Cardiopulmonary Resuscitation - Fletcher, Daniel J.; Boller, Manuel (Frontiers in Veterinary Science, 2021)
Cardiopulmonary arrest (CPA), the acute cessation of blood flow and ventilation, is fatal if left untreated. Cardiopulmonary resuscitation (CPR) is targeted at restoring oxygen delivery to tissues to mitigate ischemic injury and to provide energy substrate to the tissues in order to achieve return of spontaneous circulation (ROSC). In addition to basic life support (BLS), targeted at replacing the mechanical aspects of circulation and ventilation, adjunctive advanced life support (ALS) interventions, such as intravenous fluid therapy, can improve the likelihood of ROSC depending on the specific characteristics of the patient. In hypovolemic patients with CPA, intravenous fluid boluses to improve preload and cardiac output are likely beneficial, and the use of hypertonic saline may confer additional neuroprotective effects. However, in euvolemic patients, isotonic or hypertonic crystalloid boluses may be detrimental due to decreased tissue blood flow caused by compromised tissue perfusion pressures. Synthetic colloids have not been shown to be beneficial in patients in CPA, and given their documented potential for harm, they are not recommended. Patients with documented electrolyte abnormalities such as hypokalemia or hyperkalemia benefit from therapy targeted at those disturbances, and patients with CPA induced by lipid soluble toxins may benefit from intravenous lipid emulsion therapy. Patients with prolonged CPA that have developed significant acidemia may benefit from intravenous buffer therapy, but patients with acute CPA may be harmed by buffers. In general, ALS fluid therapies should be used only if specific indications are present in the individual patient.